The Portrayal of Woman in Selected Contemporary Fairy Tales - Krsková, Helena (Univerzita Pardubice, 2018)
The main purpose of this thesis is to provide an analysis of the woman's portrayal in selected contemporary fairy tales. In the initial part of the thesis the definition of the genre and its broader literary context are introduced. Further, the depiction of a woman in traditional fairy tales is examined and the overview of the most significant literary theories is presented. A special attention is paid to feminist literary theory since it is the essential theory for the analysis. The analytical part explores female characters and their roles in relation to the traditional woman's depiction. The conclusion summarises the discoveries.
Obraz žen ve vybraných současných pohádkách
Keywords: feministická literární teorie; genderové stereotypy; role ženy; současné pohádky; patriarchální společnost; feminist literary theory; gender stereotypes; female role; contemporary fairy tales; patriarchal society